1. The problem statement, all variables and given/known data Find the particular solution to the initial value problem: (3xy - 4x - 1)dy + y(y - 2)dx = 0; when x=1, y=2 2. Relevant equations dy + (p(x)y - q(x))dx = 0 e^(-∫p(x)dx) * (c + ∫e^(∫p(x)dx) * q(x)dx) 3. The attempt at a solution Sorry if this is vague, but I just spent 30 min typing out the entire process only to have it deleted. This is where I got stuck: p(y) = 3y - 4 / y(y - 2) q(y) = 1 / y(y - 2) x = [y^(1/2) / (y-2)^(1/2)] * (c + ∫dy/[y^(3/2) * (y - 2)^(1/2)]) I don't know how to do the remaining integral. I think it's partial fractions but the y^(3/2) is confusing me.